PENGARUH MINAT DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR NIRMANA 3 DIMENESI PADA MATA PELAJARAN SENI BUDAYA DI SMP NEGERI 2 PADANG PANJANG - Damayanti, Alfina; Iswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of learning interest and creativity on students’ learning outcomes in Nirmana 3 dimensional within the Arts and Culture subject for seventh-grade students at SMP Negeri 2 Padangpanjang. The research employed a quantitative approach with a correlational design and involved 119 students as the research population. Data were collected through closed-ended questionnaires to measure students’ learning interest and creativity, while learning outcome data were obtained through score documentation. The research instruments were tested for validity and reliability to ensure their appropriateness. The collected data were analyzed using normality tests, linearity tests, and regression analysis. The findings indicate that both learning interest and creativity individually have a significant effect on students’ learning outcomes in Nirmana 3D. Furthermore, both variables simultaneously show a significant effect on learning outcomes. Therefore, learning interest and creativity are important factors that should be fostered in the learning process to improve students’ academic achievement.